COVID-19 and the risk of neuromyelitis optica spectrum disorder: a Mendelian randomization study - Sun, Dongren; Du, Qin; Wang, Rui; Shi, Ziyan; Chen, Hongxi; Zhou, Hongyu (Frontiers in Immunology, 2023)
Background: An increasing number of studies has elucidated a close nexus between COVID-19 phenotypes and neuromyelitis optica spectrum disorder (NMOSD), yet the causality between them remains enigmatic. Methods: In this study, we conducted a Mendelian randomization (MR) analysis employing summary data sourced from genome-wide association studies (GWAS) pertaining to COVID-19 susceptibility, hospitalization, severity, and NMOSD. The primary MR analysis employed the Inverse variance weighted (IVW) approach, which was supplemented by MR-Egger, weighted median, simple mode, and weighted mode methods. We implemented various sensitivity analyses including Cochran's Q test, MR-PRESSO method, MR-Egger intercept, leave-one-out analysis, and funnel plot. Results: The MR results demonstrated a nominal association between COVID-19 susceptibility and the risk of AQP4+ NMOSD, as evidenced by the IVW method (OR = 4.958; 95% CI: 1.322-18.585; P = 0.018). Conversely, no causal association was observed between COVID-19 susceptibility, hospitalization, or severity and the increased risk of NMOSD, AQP4-NMOSD, or AQP4+ NMOSD. The comprehensive sensitivity analyses further bolstered the robustness and consistency of the MR estimates. Conclusion: Our findings provide compelling evidence for a causal effect of COVID-19 phenotype on AQP4+ NMOSD, shedding new light on the understanding of the comorbidity between COVID-19 and NMOSD.